2021
DOI: 10.1039/d0nr07660k
|View full text |Cite|
|
Sign up to set email alerts
|

Stacking of nanorings to generate nanotubes for acceleration of protein refolding

Abstract: Refolding of denatured proteins effectively occurred simultaneously with release from a long and narrow nanotube, which is formed by uniaxial stacking of nanorings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 126 publications
0
6
0
Order By: Relevance
“…The advantages of such nanotubes are that the diameters of their nanochannels are tunable to less than several tens of nanometers within an error range of a few nanometers and that their inner surfaces are designable with respect to the presentation of functional groups . Such supramolecular nanotubes have been used as templates for the construction of inorganic or metal nanostructures through sol–gel reactions and for the reduction of inorganic precursors and metal ions adsorbed on the surface of, or encapsulated in, the nanochannels. Confinement effects of the supramolecular nanotubes against proteins and DNAs are useful for maintaining the folded structures of proteins, supporting the refolding of denatured proteins, , or accelerating the duplex formation of DNAs. , More recently, our group has found that the morphologies of π-conjugated polymers with rigid backbones can be controlled when the polymers synthesized in advance in bulk media are encapsulated within supramolecular nanotubes or the polymerization reaction of the encapsulated monomers is performed within supramolecular nanotubes . More specifically, we found that polythiophene that existed as a random coil in bulk solution took on a one-dimensional extended morphology when encapsulated within supramolecular nanotubes with narrow nanochannels, whereas it took on an aggregated morphology when encapsulated within wider nanochannels.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The advantages of such nanotubes are that the diameters of their nanochannels are tunable to less than several tens of nanometers within an error range of a few nanometers and that their inner surfaces are designable with respect to the presentation of functional groups . Such supramolecular nanotubes have been used as templates for the construction of inorganic or metal nanostructures through sol–gel reactions and for the reduction of inorganic precursors and metal ions adsorbed on the surface of, or encapsulated in, the nanochannels. Confinement effects of the supramolecular nanotubes against proteins and DNAs are useful for maintaining the folded structures of proteins, supporting the refolding of denatured proteins, , or accelerating the duplex formation of DNAs. , More recently, our group has found that the morphologies of π-conjugated polymers with rigid backbones can be controlled when the polymers synthesized in advance in bulk media are encapsulated within supramolecular nanotubes or the polymerization reaction of the encapsulated monomers is performed within supramolecular nanotubes . More specifically, we found that polythiophene that existed as a random coil in bulk solution took on a one-dimensional extended morphology when encapsulated within supramolecular nanotubes with narrow nanochannels, whereas it took on an aggregated morphology when encapsulated within wider nanochannels.…”
mentioning
confidence: 99%
“…31 Such supramolecular nanotubes have been used as templates for the construction of inorganic or metal nanostructures through sol−gel reactions and for the reduction of inorganic precursors and metal ions adsorbed on the surface of, or encapsulated in, the nanochannels. 32−37 Confinement effects of the supramolecular nanotubes against proteins and DNAs are useful for maintaining the folded structures of proteins, 38 supporting the refolding of denatured proteins, 39,40 or accelerating the duplex formation of DNAs. 41,42 More recently, our group has found that the morphologies of π-conjugated polymers with rigid backbones can be controlled when the polymers synthesized in advance in bulk media are encapsulated within supramolecular nanotubes 43 or the polymerization reaction of the encapsulated monomers is performed within supramolecular nanotubes.…”
mentioning
confidence: 99%
“…Indeed, compared with recovery from spherical nanocapsules or nanorings (very short nanotubes), recovery from nanotubes takes much longer and the process is much less efficient. 3 To address this issue, methods to decompose or transform nanotubes to rapidly release encapsulated compounds have been proposed, and there are many reports describing supramolecular nanotubes that are decomposed or transformed in response to various stimuli such as pH, 4 salts, 5 metal ions, 6 additives, 7 solvents, 8 dilution, 9 temperature, 10 light, 11 ultrasound, 12 and electric potential. 13 However, there is little information available on the actual recovery of the encapsulated compounds from such stimuli-responsive nanotubes.…”
Section: Introductionmentioning
confidence: 99%
“…The time ( t 50 ) required to reach 50% of the maximum CD intensity (Δε 336 nm = 86 M –1 cm –1 ) was 5 min at c tot = 300 μM, which increased to 11.5 min upon decreasing the monomer concentration to 250 μM. This result reiterates that the nanotoroids directly organize into nanotubes without dissociation into monomers, i.e., the nanotoroids are intermediates on the pathway (on-pathway intermediates) to the formation of the nanotubes (Figure c). Similar non-linear growth of the CD signal was observed for scalemic (60% ee and 20% ee of 1R ) P -nanotoroids, albeit with relatively slow kinetics (Figure b). This observation suggests that the enantiomeric purity of the internal chiral side chains affects the interaction between the nanotoroids.…”
Section: Resultsmentioning
confidence: 68%